Inovasi Pengelolaan Pembelajaran Biologi Berbasis Proyek di SMA Islam Al Azhar 14 Semarang - Widiyadmi, Rini (Media Manajemen Pendidikan, 2025)
This study aims to describe the innovation in managing project-based Biology learning at SMA Islam Al Azhar 14 Semarang. Innovation in learning is essential to enhance student engagement, critical thinking skills, and deep conceptual understanding, particularly in Biology, which combines theoretical and practical components. This research employs a qualitative approach with a case study method. Data were collected through classroom observations, in-depth interviews with Biology teachers and students, and documentation of learning activities. The results indicate that the implementation of project-based learning is integrated with Islamic values through project themes related to environmental issues and Islamic teachings. The innovations include collaborative project planning, effective management of time and learning resources, and portfolio-based assessment. The main challenges faced are limited instructional time within the curriculum and students' readiness for independent work. However, through adaptive approaches and strong school support, these challenges can be mitigated. This innovation has proven to increase student motivation and strengthen 21st-century skills. The findings are expected to serve as a reference for teachers in developing contextual, active, and meaningful Biology learning strategies in Islamic-based schools.